La construcción de un marco feminista de interpretación: la violencia de género - Miguel Álvarez, Ana De (Cuadernos de Trabajo Social, 2005)
The aim of this article is to explain a double process – the rejection of the justification of violence against women and the construction of a new frame to interpret such violence. Historically the feminist movement has played the most important part in the development of this viewpoint. Firstly, I begin from a standpoint which adopts the new theories concerning social movements. These theories examine the role of social movements in creating new frames from which to interpret reality. Secondly, I outline the patriarchal interpretation of violence against women and I explain the steps involved in the construction of a new feminist frame of interpretation. Finally, I will look at some of the academic studies that have helped to legitimate the feminist view of violence against women and at how the new feminist frame has spread within Spain.